A randomised controlled trial exploring the effects of different beverages consumed alongside a nitrate-rich meal on systemic blood pressure. Issue 3 (September 2018) - McDonagh, Sinead TJ; Wylie, Lee J; Morgan, Paul T; Vanhatalo, Anni; Jones, Andrew M
Background: Ingestion of nitrate (NO3 - )-containing vegetables, alcohol and polyphenols, separately, can reduce blood pressure (BP). However, the pharmacokinetic response to the combined ingestion of NO3 - and polyphenol-rich or low polyphenol alcoholic beverages is unknown. Aim: The aim of this study was to investigate how the consumption of low and high polyphenolic alcoholic beverages combined with a NO3 - -rich meal can influence NO3 - metabolism and systemic BP. Methods: In a randomised, crossover trial, 12 normotensive males (age 25 ± 5 years) ingested an acute dose of NO3 - (∼6.05 mmol) in the form of a green leafy salad, in combination with either a polyphenol-rich red wine (NIT-RW), a low polyphenol alcoholic beverage (vodka; NIT-A) or water (NIT-CON). Participants also consumed a low NO3 - salad and water as a control (CON; ∼0.69 mmol NO3 - ). BP and plasma, salivary and urinary [NO3 - ] and nitrite ([NO2 - ]) were determined before and up to 5 h post ingestion. Results: Each NO3 - -rich condition elevated nitric oxide (NO) biomarkers when compared with CON ( P < 0.05). The peak rise in plasma [NO2 - ] occurred 1 h after NIT-RW (292 ± 210 nM) and 2 h after NIT-A (318 ± 186 nM) and NIT-CON (367 ± 179 nM). Systolic BP was reduced 2 h post consumption of NIT-RW (-4 mmHg), NIT-A (-3 mmHg) and NIT-CON (-2 mmHg) compared with CON ( P < 0.05). Diastolic BP and mean arterial pressure were also lower in NIT-RW and NIT-A compared with NIT-CON ( P < 0.05). Conclusions: A NO3 - -rich meal, consumed with or without an alcoholic beverage, increases plasma [NO2 - ] and lowers systemic BP for 2–3 h post ingestion.